FTA informs the calculation of Indonesia's Forest Reference Emission Levels - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
Methods suggested by CIFOR-ICRAF scientists were adopted for the calculation of Indonesia’s 2nd Forest Reference Emission Levels (FRELs) to be submitted to the UNFCCC in early 2022